2019
DOI: 10.1007/s00586-019-06220-w
|View full text |Cite
|
Sign up to set email alerts
|

The contradictory effect of macrophage-related cytokine expression in lumbar disc herniations: a systematic review

Abstract: Purpose Sciatic symptoms due to lumbar disc herniation are likely to be caused not solely by mechanical compression of the nerve root, but also by pain-inducing elements from inflammatory processes. Key components in the inflammatory reaction are M1 and M2 macrophages, with the M1 type being associated with pro-inflammatory processes and M2 with anti-inflammatory-processes. Method The present systematic review summarizes all studies on associations between M1 and M2 macrophages and their related inflammation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…M2 is believed to alleviate pain symptoms through resorption of herniated disc material. During most inflammation processes, M1 or M2 macrophages occur sequentially [31][32][33][34]. Cytokines excreted during the process of disc herniation in sciatica seem to have a different effect on pain symptoms.…”
Section: Natural Evolution Of Extruded Disc Herniationmentioning
confidence: 99%
See 1 more Smart Citation
“…M2 is believed to alleviate pain symptoms through resorption of herniated disc material. During most inflammation processes, M1 or M2 macrophages occur sequentially [31][32][33][34]. Cytokines excreted during the process of disc herniation in sciatica seem to have a different effect on pain symptoms.…”
Section: Natural Evolution Of Extruded Disc Herniationmentioning
confidence: 99%
“…Cytokines excreted during the process of disc herniation in sciatica seem to have a different effect on pain symptoms. Pro-inflammatory cytokines worsen pain symptoms, while anti-inflammatory cytokines alleviate pain symptoms [34] (Figure 1).…”
Section: Natural Evolution Of Extruded Disc Herniationmentioning
confidence: 99%
“…( 17)IL-1 is produced by monocytes and macrophages in the form of a proprotein, which is proteolytically processed and released in response to cell injury, thus inducing apoptosis [32]. Moreover, the IL1A gene has been previously identified to carry a threefold risk of disc bulges compared to controls [9,33]. It has been shown that an increased level of the pro-inflammatory IL1A antagonizes IL-1 receptor antagonist (IL1RN) in the degenerated disc as there is a dysregulation about tissue destruction [27].…”
Section: Interleukin-1mentioning
confidence: 99%
“…It is caused not solely by mechanical compression of the nerve root but also by the release of many inflammatory molecules ( Takahashi et al, 1996 ; Ahn et al, 2002 ; Scuderi et al, 2006 ; Pedersen et al, 2015 ). Clinical data indicate that 20–76% of nerve root compression due to a disc herniation is painless, and some cases with slight disc herniation suffer severe pain ( Takada et al, 2001 ; Djuric et al, 2020 ). Therefore, a chemical factor may play an important role in radicular leg pain, following lumbar disc herniation ( Andrade et al, 2013 ; Hasvik et al, 2019 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%